Glucose fluctuations promote vascular BK channels dysfunction via PKCα/NF-κB/MuRF1 signaling. (August 2020) - Zhang, Zhen-Ye; Qian, Ling-Ling; Wang, Ning; Miao, Ling-Feng; Ma, Xin; Dang, Shi-Peng; Wu, Ying; Liu, Xiao-Yu; Li, Xiao-Yan; Chai, Qiang; Pan, Min; Yi, Fu; et al.
Abstract: Glucose fluctuations may contribute to large conductance calcium activated potassium (BK) channel dysfunction. However, the underlying mechanisms remain elusive. The aim of this study was to investigate the molecular mechanisms involved in BK channel dysfunction as a result of glucose fluctuations. A rat diabetic model was established through the injection of streptozotocin. Glucose fluctuations in diabetic rats were induced via consumption and starvation. Rat coronary arteries were isolated and coronary vascular tensions were measured after three weeks. Rat coronary artery smooth muscle cells were isolated and whole-cell BK channel currents were recorded using a patch clamp technique. Human coronary artery smooth muscle cells in vitro were used to explore the underlying mechanisms . After incubation with iberiotoxin (IBTX), the Δ tensions (% Max) of rat coronary arteries in the controlled diabetes mellitus (C-DM), the uncontrolled DM (U-DM) and the DM with glucose fluctuation (GF-DM) groups were found to be 84.46 ± 5.75, 61.89 ± 10.20 and 14.77 ± 5.90, respectively ( P  < .05), while the current densities of the BK channels in the three groups were 43.09 ± 4.35 pA/pF, 34.23 ± 6.07 pA/pF and 17.87 ± 4.33 pA/pF, respectively ( P  < .05). The Δ tensions (% Max) of rat coronary arteries after applying IBTX in the GF-DM rats injected with 0.9% sodium chloride (NaCl) (GF-DM + NaCl) and the GF-DM rats injected with N-acetyl-L-cysteine (NAC) (GF-DM + NAC) groups were found to be 8.86 ± 1.09 and 48.90 ± 10.85, respectively ( P  < .05). Excessive oxidative stress and the activation of protein kinase C (PKC) α and nuclear factor (NF)-κB induced by glucose fluctuations promoted the decrease of BK-β1 expression, while the inhibition of reactive oxygen species (ROS), PKCα, NF-κB and muscle ring finger protein 1 (MuRF1) reversed this effect. Glucose fluctuations aggravate BK channel dysfunction via the ROS overproduction and the PKCα/NF-κB/MuRF1 signaling pathway. Graphical abstract: Illustration showing the role of PKCα/NF-κB/MuRF1 signaling in the regulation of BK channel in response to glucose fluctuation. Under conditions of glucose fluctuations, there is an activation of PKC, which in turn promotes NF-κB/p65 nuclear translocation, facilitates MuRF1-dependent BK-β1 protein degradation. Unlabelled Image Highlights: Glucose fluctuations aggravate coronary vasodilation dysfunction. BK channels are impaired by BK-β1 degradation due to glucose fluctuations. ROS overproduction is enhanced by glucose fluctuations. Glucose fluctuations activate PKCα/NF-κB/MuRF1 signaling pathway.